Septic shock caused by postpartum acute pancreatitis, a case report and literature review - Changiz Delavari; Delaram J. Ghadimi; Maryam Taheri; Harsh Kumar; Pouya Ebrahimi; Amir Nasrollahizadeh; Sepide Javankiani (International Journal of Emergency Medicine)
Abstract Introduction Postpartum acute pancreatitis (PAP) is a rare but potentially life-threatening condition that can occur following childbirth. The incidence of PAP is estimated to be between 1 in 1,000 and 1 in 10,000 deliveries, with a significant proportion of cases linked to biliary causes, particularly gallstones and biliary sludge. Prompt diagnosis and comprehensive management are essential to prevent severe complications such as septic shock and peritonitis. Case presentation We report the case of a 25-year-old white woman who presented with severe abdominal pain and septic shock 18 days after a cesarean section. Initial management included aggressive fluid resuscitation, broad-spectrum antibiotics, and pain control. Diagnostic imaging and laboratory tests confirmed the presence of biliary obstruction due to gallstones and biliary sludge, leading to acute pancreatitis. An endoscopic retrograde cholangiopancreatography (ERCP) was performed to remove the biliary obstructions, followed by a laparoscopic cholecystectomy to prevent recurrence. Discussion PAP, while rare, poses significant risks and can lead to serious side effects such as septic shock. Early diagnosis by laboratory workup and imaging is essential. In this instance, gallstones and biliary sludge were found to be the culprit, requiring cholecystectomy and ERCP. ERCP was effective in this patient, despite its controversy in septic patients. The effective management of PAP requires a multidisciplinary approach involving obstetricians, gastroenterologists, surgeons, and critical care specialists. Conclusion PAP must be identified and treated as soon as possible. Bile obstruction is a common problem that necessitates prompt imaging and, if necessary, endoscopic or surgical intervention. Delays can be fatal; timing is crucial. To prevent deadly consequences, doctors must be extremely suspicious of postpartum patients presenting with abdominal pain.